2018
DOI: 10.1177/1088767918807252
|View full text |Cite
|
Sign up to set email alerts
|

Homicides and Weapons: Examining the Covariates of Weapon Choice

Abstract: This study examines the covariates of weapon choice in homicide incidents. Two research questions are examined. The first research question is: what variables influence the use of a particular type of weapon in a homicide? The second research question asks: how does the method of weapon retrieval, or lack thereof, affect the choice of weapon? The findings suggest that firearms are more likely to be on the offender’s person and carried to the incident scene relative to other weapon types. In addition, the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Compared to other homicide types, a smaller percentage of IPH involve firearms, while a higher percentage involve strangulation, suffocation, or knives (Fox & Allen, 2013;Matias et al, 2020;Spencer & Stith, 2020;Thomas et al, 2011). However, a recent study found that domestic homicides and homicides with other motives were just as likely to involve firearms (Pelletier & Pizarro, 2019). Thus, incidents stemming from domestic disputes are significantly more likely to involve a firearm on-scene, as opposed to the offender leaving the scene to retrieve a firearm or having a firearm delivered (Pelletier & Pizarro, 2019).…”
Section: Situational Characteristicsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared to other homicide types, a smaller percentage of IPH involve firearms, while a higher percentage involve strangulation, suffocation, or knives (Fox & Allen, 2013;Matias et al, 2020;Spencer & Stith, 2020;Thomas et al, 2011). However, a recent study found that domestic homicides and homicides with other motives were just as likely to involve firearms (Pelletier & Pizarro, 2019). Thus, incidents stemming from domestic disputes are significantly more likely to involve a firearm on-scene, as opposed to the offender leaving the scene to retrieve a firearm or having a firearm delivered (Pelletier & Pizarro, 2019).…”
Section: Situational Characteristicsmentioning
confidence: 97%
“…However, a recent study found that domestic homicides and homicides with other motives were just as likely to involve firearms (Pelletier & Pizarro, 2019). Thus, incidents stemming from domestic disputes are significantly more likely to involve a firearm on-scene, as opposed to the offender leaving the scene to retrieve a firearm or having a firearm delivered (Pelletier & Pizarro, 2019). Indeed, offenders appear to remain near the scene during domestic disputes and thus use a weapon that is readily available (Corsaro et al, 2017).…”
Section: Situational Characteristicsmentioning
confidence: 99%
“…Similarly, it has been found that, as the aggressor’s age increases, there is a greater tendency to use bladed weapons and blunt objects [32]. Likewise, Khoshnood and Väfors Fritz [33] revealed that perpetrators between the ages of 37 and 59 are associated with non-premeditated-approach methods, thus these homicides tend to be triggered by arguments.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, it has been shown that in the case of perpetrators who previously knew their victims, there tends to be a greater number and seriousness of injuries [41], with the homicides tending to take place indoors and most often using bladed weapons or blunt objects [32,42]. In addition, they tend to be triggered by an argument [33,43]; similarly, the victims are usually male and between the ages of 15 and 24 [44].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation